Penguasaan kemahiran generik di kalangan pelajar dalam memenuhi kehendak industri : IPTA dan IPTS - Arshad, Nazni Hani (2007)
This study was conducted in order to identify and compare the generic skill competency among the IPTA and IPTS' student in term of fulfill the industrial needs. There are 386 responders from final semester degree from selected IPTA and IPTS and also two respondent's representative industries. This study also conducted in order to identify the student's awareness in the generic skills, to identify their competence in the generic skill, and to identify the differential of generic skill competency between IPTA and IPTS students and requirements from the industries. Questionnaires and interview is used as the instruments. SPSS v. 11.0 is used to analyze the data and was shown in the form of mean score, variance, factor analysis and independent t-test. Overall, the findings show that the students from both institutes have a high attention in term of their generic skill which the mean score are IPTA1 = 4.54, EPTA2 = 4.48, IPTS1 = 4.27 and IPTS2 = 4.60. They also have a high competency of generic skill which the mean score are IPTA1 = 4.29, IPTA2 = 4.24, IPTS1 = 3.99 dan IPTS2 = 4.19. By the way, the mean score for IPTA students is higher than the IPTS's students where IPTA = 4.27 and IPTS = 4.09. Therefore, hopefully this study's finding can help the IPTA and IPTS administration involved in order to identify the generic skills that owned by their students and the requirements from the industries as well.